Miscibility and specific interactions in blends of poly[(styrene)-co-(cinnamic acid)] with poly(methyl methacrylate) and modified poly(methyl methacrylate) (eXPRESS Polymer Letters)
The miscibility behavior of poly(styrene-co-cinnamic acid) (PSCA) with poly(methyl methacrylate) (PMMA), poly[(methyl methacrylate)-co-(4-vinylpyridine)] (PMMA4VP) and poly[(methyl methacrylate)-co-(2-vinylpyridine)] (PMMA2VP) was studied. DSC measurements indicated that PSCA23 containing 23 mol% of carboxylic acid units was miscible with PMMA, PMMA2VP and PMMA4VP as established from the observation of a single composition dependent glass transition temperature. Miscibility was induced via hydrogen bonding as evidenced by IR frequency shifts of the hydroxyl stretching vibrations of the acid copolymer in the blends. Interpolymer hydrogen bonding formation within the binary systems was also investigated by viscosimetric study of dilute solutions in toluene. For PMMA/PSCA5 blends the viscosity of the mixtures was close to the weight average viscosities of the individual polymer while for blend solutions of PSCA5 with PMMA2VP and PMMA4VP, the interactions were sufficiently strong to form interpolymer complexes with a decrease in viscosity in comparison to the additivity rule.